2015
DOI: 10.1007/s12011-015-0381-9
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Bafilomycin A1 Against Cobalt Nanoparticle-Induced Cytotoxicity and Aseptic Inflammation in Macrophages In Vitro

Abstract: Co ions released due to corrosion of Co nanoparticles (CoNPs) in the lysosomes of macrophages may be a factor in the particle-induced cytotoxicity and aseptic inflammation accompanying metal-on-metal (MOM) hip prosthesis failure. Here, we show that CoNPs are easily dissolved under a low pH, simulating the acidic lysosomal environment. We then used bafilomycin A1 to change the pH inside the lysosome to inhibit intracellular corrosion of CoNPs and then investigated its protective effects against CoNP-induced cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Oxidative stress is currently believed to be the main modulator of adverse effects upon exposure to nanoparticles [ 13 , 27 , 28 , 29 ]. Previous studies have shown that exposure to nanoparticles could induce intracellular oxidative stress by disturbing the balance between the oxidant and antioxidant processes [ 30 ]. However, not much is known regarding the oxidative stress caused by QDs in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is currently believed to be the main modulator of adverse effects upon exposure to nanoparticles [ 13 , 27 , 28 , 29 ]. Previous studies have shown that exposure to nanoparticles could induce intracellular oxidative stress by disturbing the balance between the oxidant and antioxidant processes [ 30 ]. However, not much is known regarding the oxidative stress caused by QDs in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, changing the acidic environment inside the lysosome using Bafilomycin A1 protects the viability of RAW264.7 cells and suppresses Co NP-induced aseptic inflammation by inhibiting intracellular Co NP corrosion and Co ions release. 102 The cytotoxic and inflammatory effects of Co NPs (28 nm) on macrophages were also observed by Nyga et al This effect is dependent on hypoxia-inducible factor (HIF), a ROS-independent pathway. 103 Notably, it is Co NPs, but not Cr NPs, which inhibit macrophage migration both in vitro and in vivo by promoting adhesion at non-cytotoxic concentrations; this is associated with ROS-RhoA signaling pathway.…”
Section: Metal Npsmentioning
confidence: 62%
“…In this range, it won't change body fluid environment (7-7.4) or induce aseptic inflammation, which is caused by a low pH value of the body fluid environment, can be avoided. 40 It is also relevant to bone metabolic pro-cess; a relatively low pH is ill-suited to bone metabolism and mineralization. 41 Morphology of composite cements during in vitro drug release Figure 7 shows the surface morphology and composition of composite cements.…”
Section: Results and Discussion Characterization Of The Tio 2 Microsphmentioning
confidence: 99%